Mission as Ministry of Reconciliation - Schreiter, Robert J. (Edinburgh Centenary., 2013)
There is hope - even if it is "Hope in a Fragile World", as the concluding chapter of Mission as Ministry of Reconciliation puts it. At the very heart of the gospel of Jesus Christ is a message of hope and reconciliation. Nothing could be more relevant and more necessary in a broken world than this Christian message of hope and reconciliation. ... I would like to congratulate the editors of Mission as Ministry of Reconciliation, for they listened carefully and planned with farsightedness. ... This rich book offers a valuable elucidation of the importance and the understanding of mission as minis.